The Influence of Picture Card Learning Media on Arabic Speaking Skills: A True Experimental Study - Khoirunnisa, Khoirunnisa; Fauji, Imam (Indonesian Journal of Islamic Studies, 2023)
This study aimed to investigate the influence of picture card learning media on Arabic speaking skills and determine the significance and correlation between them among seventh-grade female students at the Integrated Islamic Junior High School Darul Fikri in Sidoarjo. The research employed a quantitative approach with a True Experimental design. The collected data were analyzed using correlation analysis. The findings indicated that the average score for Arabic speaking skills in the experimental group was 82.15, falling under the "good" category, while the control group scored an average of 79.45, categorized as "satisfactory." The hypothesis testing results demonstrated that there was no significant influence of picture card learning media on Arabic speaking skills among seventh-grade female students at the Integrated Islamic Junior High School Darul Fikri in Sidoarjo (t-value ≤ t-critical, 1.650 ≤ 2.013, α = 0.05). Therefore, it can be interpreted that the picture card learning media did not have an impact on Arabic speaking skills in this context. The study utilized a quantitative research method, specifically a True Experimental design, with a random selection of participants into experimental and control groups. The data were collected through a posttest, and the statistical analysis employed the t-test. The research results provide insights for educators and curriculum developers to reconsider the effectiveness of picture card learning media in enhancing Arabic speaking skills among female students. Highlight: The study aimed to investigate the influence of picture card learning media on Arabic speaking skills among seventh-grade female students in an integrated Islamic school. The research adopted a quantitative approach with a True-experimental design, focusing on correlation analysis. The results showed that there was no significant influence of picture card learning media on Arabic speaking skills among the students. Keyword: Arabic Speaking Skills, Picture Card Learning Media, True-Experimental, Correlation, Secondary School